Variability of the structure of correlations between the morphological and commercial traits of soybeans with different growth habit and branching characters - M. O. Burlyaeva; N. S. Rostova (Вавиловский журнал генетики и селекции, 2019)
High yields of seeds,  green  pods  and  green  biomass  is the  main goal of soybean breeding in many  countries. An assessment of relationships between the  productivity traits  and  their  effect  on the  yield may be  useful in developing effective crop cultivation  programs. In soybean,  the stem  growth  habit  and the branching character are interrelated with plant  productivity and  in most  cases determine it. Therefore, the  aim of the  present work was to study  the  variability of the  level (strength) and  the  structure of correlations between 92 morphological, phenological, biochemical,  agronomic traits of soybean accessions  with different  growth  habits,  and  branching characters in different weather conditions. 270 soybean accessions  of different ecological and geographical origin from the VIR collection  have  been  grown  in the  Krasnodar region  within 3 years. Field studies  of the  traits and biochemical  analysis were carried out according to VIR guidelines. The variability of correlation  matrices as regards the  strength and  structure of relationships was analyzed  using the  correlation  and  factor analysis (the principal component method), as well as the method developed by N.S. Rostova. A comparison of the level (R2, coefficient of determination) and  structure of correlations in different  years has  shown  that  the  deterioration of external conditions is followed by an increase  in the strength of relationships (R2) between the traits and in the difference between correlation   matrices’ structure. Soybean  adaptation to  the  changing  conditions occurs  due  to  the rearrangements of relationship systems, whereas  the  degree and direction  of these  changes are determined by the  growing  conditions and  specificity of the  accessions  response. Under favorable  conditions, the  structure of correlations in soybeans with different  growth  habits,  and  branching characters has more  similarity than  in the conditions critical for development. The highest level of relationships (R2) between the traits was observed in the year that was unfavorable for the growth  of the semi-cultivated accessions  (with the indeterminate growth  habit and a large number of branches of the 1st and 2nd order). The green  biomass  productivity of accessions  with the determinate growth  habit and more than two branches is most strongly associated with the branch  weight, while in accessions  with the indeterminate growth  habit and with (or without) 1–2 branches it depends on the growing season  duration,  one leaf weight  and the number of leaves per plant. In the semi-cultivated accessions  (with the indeterminate growth habit and numerous branches of the 1st and 2nd order), it correlates, besides the listed traits, with the number of nodes, the internode length, the main stem diameter, the weight of leaves, seed morphometric parameters and their quality.